Isolation of Microsporum canis from the hair coats of shelter cats in the southeast of Brazil (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2014)
All over the world asymptomatic cats are considered the main reservoirs and sources of infection of dermatophytes, especially Microsporum canis. In humans, 15% of tinea cases have zoonotic origin, and often involves contact with cats with no skin lesions.